The Effectiveness of Graphic Organizer As A Media in Teaching Students’ Writing Project - Suprimarni, Ani (English Language, Linguistics, Literature, And Education Journal, 2021)
A Graphic Organizer (GO) is quite a creative media expresses the text concepts. It is an instructional tool that can help students to organize, structured the information and concepts to relate with the other concepts. Graphic organizers display information, structure, and key conceptual relationships using visual and spatial arrangements or maps. Graphic organizers often involve lines, arrows, text boxes or bubbles, pictures, and other visual depictions to represent ideas, facts, and concepts. The implementation of Graphic Organizer is aimed at increasing the students’ ability in writing narrative text for grade ninth at SMPN 1 Merlung. The previous learning used students’ task learning as method in learning writing which unmatched with the needs of students in facing challenging of writing text. The research was conducted to the ninth graders of SMPN 1 Merlung with total 62 students by giving treatment in control and experimental group. The data were the students’ writing in the pre-test and post-test. To count the data, the researcher used t-test and SPSS. Based on the counting, it was found that the value of t-test at the degree of freedom 60 and the level of significance 0.05 was 7.012 which is value of t-test is higher than value of t-table (7.012> 2.000). It means that the Null Hypothesis is rejected and the alternative hypothesis is accepted. Thus, it proved that there is effect of using graphic organizer on students’ writing project. Since the graphic organizer media had significant effect to the students’ writing abilities, so this media can be used as one of the alternative technique for English teacher in teaching writing narrative text.